Infrastructure and Technology Management Contributions from the Energy, Healthcare and Transportation Sectors (Cham : Springer International Publishing, 2018)
This book presents emerging technology management approaches and applied cases from leading infrastructure sectors such as energy, healthcare, transportation and education. Featuring timely topics such as fracking technology, electric cars, Google's eco-friendly mobile technology and Amazon Prime Air, the volume's contributions explore the current management challenges that have resulted from the development of new technologies, and present tools, applications and frameworks that can be utilized to overcome these challenges. Emerging technologies make us rethink how our infrastructure will look in the future. Solar and wind generation, for example, have already changed the dynamics of the power sector. While they have helped to reduce the use of fossil fuels, they have created management complications due to their intermittent natures. Meanwhile, information technologies have changed how we manage healthcare, making it safer and more accessible, but not without implications for cost and administration. Autonomous cars are around the corner. On-line education is no longer a myth but still a largely unfulfilled opportunity. Digitization of car ownership is achievable thanks to emerging business models leveraging new communication technologies. The major challenge is how to evaluate the relative costs and benefits of these technologies. This book offers insights from both researchers and industry practitioners to address this challenge and anticipate the impact of new technologies on infrastructure now and in the future.
Part I Energy -- Chapter 1 Landscape Analysis: Regulations, Policies and Innovation in Photovoltaic Industry -- Chapter 2 Landscape Analysis: Fracking Technology -- Chapter 3 Landscape Analysis: Connected-Lighting System -- Chapter 4 Technology Assessment: Developing Geothermal Energy Resources for Supporting Electrical System in Oregon -- Chapter 5 Technology Assessment: Demand Response Technologies in the Pacific Northwest.- Part II Health Care -- Chapter 6 Landscape Analysis: What Are the Forefronts of Change in the US Hospitals? -- Chapter 7 Technology Assessment: Patient-Centric Solutions for Transfer of Health Information -- Chapter 8 Technology Assessment: Nosocomial Infection Solutions -- Chapter 9 Technology Assessment: Study of User Preferences for Weight Loss Mobile Applications both Globally and in the United States.- Part III Transportation -- Chapter 10 Landscape Analysis: The Electric Car - is it a Viable Alternative? -- Chapter 11 Technology Roadmap: A roadmap for TESLA -- Chapter 12 Technology Roadmap: Google's Eco-Friendly Mobile Phones -- Chapter 13 Technology Roadmap: Drone Delivery - Amazon Prime Air -- Chapter 14 Technology Assessment: Emerging Automotive Technologies for the Future -- Part IV Infrastructure -- Chapter 15 Technology Assessment: The Evaluation of Residential Pool Sanitation Options using TOPSIS.- Chapter 16: Technology Assessment: Cloud Service Adoption Decision.- Chapter 17: Project Delivery: Highway Construction.
Business and Management
text file PDF
Keywords: Management; Industrial management; Economic policy; Health care management; Health services administration; Transportation